Diary by E. G. Hawkesworth, Nso, Nsungli Area, Bamenda Division (Colonial Letters and the Contact of Knowledges, 1922)
This file contains a colonial diary by Hawkesworth on Nso, Nsungli Area, Bamenda Division, Cameroons Procinve
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies